2023
DOI: 10.1007/s40122-023-00489-y
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain and Radiofrequency Denervation of Facet Joint: Beyond Pain Control—A Video Recording

Abstract: Chronic low back pain is often due to L5S1 instability resulting in facet joint syndrome. Patients suffering from low back pain may also have a gait pattern characterized by a reduced speed and a shorter, asymmetrical step in order to reduce pain. This case is of a patient with L5S1 instability that occurred after L1 to L5 lumbar stabilization who was treated with radiofrequency (RF) denervation of the medial branch of L5S1 bilaterally. RF ablation outcome was tested by comparing its impact on pain, function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Research by Enrico Ballestra et al suggested that the effectiveness of conservative treatment in patients is correlated with the patients' subjective experiences during the treatment process [24]. In addition, radiofrequency, as a minimally invasive surgical technique, has been proven to provide significant relief from lower back pain caused by degenerative lumbar conditions [25,26]. However, for patients with surgical indications, surgical treatment remains the most effective method for alleviating symptoms of degenerative lumbar diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Enrico Ballestra et al suggested that the effectiveness of conservative treatment in patients is correlated with the patients' subjective experiences during the treatment process [24]. In addition, radiofrequency, as a minimally invasive surgical technique, has been proven to provide significant relief from lower back pain caused by degenerative lumbar conditions [25,26]. However, for patients with surgical indications, surgical treatment remains the most effective method for alleviating symptoms of degenerative lumbar diseases.…”
Section: Discussionmentioning
confidence: 99%